Liudmyla Lonska: SPECIFICITY OF MANIFESTATION OF GRAMMATICAL CATEGORIES OF NAMED PARTS OF LANGUAGE (BASED ON THE STORY BY MYKHAILO KOTSYUBYNSKY «SHADOWS OF FORGOTTEN ANCESTORS») - Lonska, Liudmyla (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. The article is devoted to the analysis of grammatical categories of noun parts of speech – noun, pronoun, numerator: case, genus, number. The purpose of the article is to investigate the specifics of the manifestation of grammatical categories of noun parts of speech in the projection on the functioning of language units in modern language. Research methods. The main method was descriptive with modeling elements used to establish morphological structures, schemes for constructing units with noun, pronoun and numeral components. The method of functional analysis was used to interpret the analyzed units in the text. The method of transformational analysis was chosen to compare the constructions that occur in the text with the syntactic units of literary language or constructions that are rarely used in modern language. Results. The analysis of the factual material made it possible to distinguish within the noun specific categories of case and gender, one case – the category of number; within the pronoun – the category of the case, which is represented by archaic forms; truncated prepositional and prepositional forms. Among the numerals found forms that have a non-normative nature of compatibility with nouns. The scientific novelty of the work lies in the analysis of category of the case, which is represented by different models depending on the morphological expression of the components. The category of gender, number and declension of the noun in terms of functioning in the studied source in comparison with literary language is also analyzed. The functional approach to the analysis of language units will allow expanding the boundaries of grammatical categories of language parts. Conclusions. This study analyzes grammatical categories that differ from the normative ones or are rarely used, although they function in parallel in the modern Ukrainian literary language. The specificity of the category of case is the variety of models of morphological expression of the analyzed structures, the use of archaic or truncated singular forms. Within the category of genus, one genitive form was replaced by another. This also applies to the category of number: the use of the plural form in nouns that do not have it. The category of declension was also specific: the use of the ending of the noun of the second declension in the instrumental case instead of the ending inherent in the first declension. The grammatical categories of the verb, in particular the category of tense and manner, and the adverb, which may be a prospect for further research in the synchronous aspect, were left out.